1981
DOI: 10.1073/pnas.78.7.4289
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a membrane-associated receptor from bovine liver that binds phosphomannosyl residues of bovine testicular beta-galactosidase.

Abstract: A receptor that binds the phosphomannosyl recognition marker of bovine testicular P-galactosidase (13-D-galactoside galactohydrolase, EC 3.2.1.23) was isolated from bovine liver membranes. The receptor was extracted from crude plasma membrane preparations with Triton X-100 and immunoprecipitated as a receptor-f-galactosidase complex with anti-,B-galactosidase. The receptor was dissociated from the precipitate with mannose 6-phosphate, labeled with`RI, and purified on a (3-galactosidase-Sepharose 4B affinity ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
75
0
1

Year Published

1982
1982
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(79 citation statements)
references
References 31 publications
(39 reference statements)
3
75
0
1
Order By: Relevance
“…While initially characterized with respect to its role in lysosomal enzyme trafficking (Sahagian et al, 1981) and IGF-2 endocytosis (Tong et al, 1988), the receptor has been reported to be involved in a number of other growth-related processes including TGF-b activation (Dennis and Rifkin, 1991), growth suppression by retinoic acid (Kang et al, 1999), granzyme B-mediated cytotoxicity (Motyka et al, 2000), and uPA receptor turnover (Nykjaer et al, 1998). With the exception of granzyme B-mediated cytotoxicity, which is ruled out by the SCID mouse experiment described here, any or all of these functions could potentially be involved in tumor suppression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While initially characterized with respect to its role in lysosomal enzyme trafficking (Sahagian et al, 1981) and IGF-2 endocytosis (Tong et al, 1988), the receptor has been reported to be involved in a number of other growth-related processes including TGF-b activation (Dennis and Rifkin, 1991), growth suppression by retinoic acid (Kang et al, 1999), granzyme B-mediated cytotoxicity (Motyka et al, 2000), and uPA receptor turnover (Nykjaer et al, 1998). With the exception of granzyme B-mediated cytotoxicity, which is ruled out by the SCID mouse experiment described here, any or all of these functions could potentially be involved in tumor suppression.…”
Section: Discussionmentioning
confidence: 99%
“…The Man-6-P/IGF-2 receptor is a multifunctional protein originally characterized with respect to its role in trafficking mannose phosphorylated hydrolases to lysosomes in mammalian cells and tissues (Sahagian et al, 1981). Cloning and sequencing of the high-affinity receptor for IGF-2 led to the realization that the two receptors were the same protein (Morgan et al, 1987) that had distinct binding sites for the two ligands (Braulke et al, 1988;Kiess et al, 1988;MacDonald et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…12 and 13). Enzymes destined for lysosomes are then equipped with mannose 6-phosphate recognition markers in the Golgi apparatus (14)(15)(16)(17), bound to phosphomannosyl receptors (18)(19)(20), and transported to lysosomes. A portion of the newly formed phosphorylated lysosomal enzymes may be secreted, and a fraction thereof may be recaptured by the phosphomannosyl receptors on the cell surface.…”
Section: Discussionmentioning
confidence: 99%
“…In fibroblasts, this secretion-recapture mechanism functions as a salvage pathway, which accounts for the delivery of5-10% oftotal lysosomal enzymes to lysosomes (23). A M-6-P receptor has been purified from a variety of tissues and appears to be a single glycoprotein with an apparent molecular weight of 215,000 (24)(25), although there is one report indicating that the receptor may consist ofsmaller subunits (26). This receptor binds acid hydrolases independent ofdivalent cations.…”
mentioning
confidence: 99%